2016
DOI: 10.1093/ehjci/jev338
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) is a risk factor for aortic and mitral valvular stenosis in peripheral arterial disease

Abstract: The high prevalence of VHD is found, especially in AR and MR, and the Lp(a) level is associated with increased risks of AS and MS in patients with PAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Even more studies have now confirmed that high Lp(a) concentrations observationally and genetically represent strong causal risk factors for aortic valve calcification, stenosis, and stenosis progression (218)(219)(220)(221)(222)(223). This is true for Whites and Asians alike.…”
Section: Atherosclerotic Stenosismentioning
confidence: 94%
“…Even more studies have now confirmed that high Lp(a) concentrations observationally and genetically represent strong causal risk factors for aortic valve calcification, stenosis, and stenosis progression (218)(219)(220)(221)(222)(223). This is true for Whites and Asians alike.…”
Section: Atherosclerotic Stenosismentioning
confidence: 94%
“…severe systemic atherosclerosis. Several studies suggested that CKD is a prognostic indicator of CVD 21,22) , and cardiovascular mortality is 10-30 times higher in patients treated with hemodialysis than in the general population 21) . Malnutrition is also an independent risk factor for mortality, with several reports showing a correlation between malnutrition and mortality in patients with CVD 5,6,23) .…”
Section: All-cause Mortalitymentioning
confidence: 99%
“…There are also hints that elevated LPA levels contribute to an increased incidence of AVS [8]. In addition, very recent studies report on a relationship between mitral valve stenosis and elevated LPA levels in patients with coexisting peripheral arterial disease [17]. …”
Section: Introductionmentioning
confidence: 99%